Racial and Ethnic Differences in Consumers' Economic Expectations. (January 2019) - Doherty Bea, Megan
Consumers' expectations about the future of their own finances and the macroeconomy are used to forecast consumption, but forecasts do not typically account for differences by race and ethnicity. In this report, the author asks (1) whether there is consistent racial and ethnic variation in consumers' economic expectations, (2) if differences can be explained by economic experiences, and (3) how the scope of expectations matters. The author uses the Survey of Consumer Finances to examine variation in the likelihood of positive national and personal economic expectations among individuals who identify as black, white, or Hispanic. The author finds that national expectations have substantial racial and ethnic variation net of economic experiences. For personal expectations, initial racial and ethnic variation in the likelihood of positive expectations disappears once economic experiences are accounted for. These findings have important implications for consumption forecasts, especially as the racial and ethnic composition of the United States changes.